Persistent Postural-Perceptual Dizziness: Precipitating Conditions, Co-morbidities and Treatment With Cognitive Behavioral Therapy - Waterston, John; Chen, Luke; Mahony, Kate; Gencarelli, Jamila; Stuart, Geoff (Frontiers in Neurology, 2021)
Persistent postural perceptual dizziness (PPPD) is a common chronic vestibular disorder characterized by persistent vestibular symptoms, including postural instability and non-spinning vertigo, which is aggravated by motion, upright posture and moving or complex visual stimuli. In our review of 198 cases seen over a 5 year period, we have confirmed a number of common precipitating conditions for PPPD, including anxiety disorders and vestibular migraine. Vestibular abnormalities, including a unilateral loss of vestibular hypofunction and isolated otolith abnormalities, were found on investigation in just under half the cases. The use of cognitive behavioral therapy (CBT) as a treatment for PPPD resulted in impressive reductions in anxiety and measures of dizziness over follow up periods of up to 6 months.